AUTOMATION OF THE JOURNAL TESTING PROCESS - LUBENCHENKO, VOLODYMYR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
An audit is a process of checking financial statements in order to confirm their reliability or compliance with the chosen conceptual basis of financial reporting. The audit process includes several stages. Firstly, this is the stage of acceptance of the client and the task, which necessarily includes the assessment by the auditor of the risks of material distortion of financial statements, including due to fraudulent actions, secondly, the stage of planning, with the definition of audit procedures in response to the assessed risks, - third, collection of audit evidence, and - fourth, reporting to the client. The article considers the process of automation of audit evidence collection in order to form the auditor’s report for financial reporting. Significant distortion of financial statements due to fraud can be connected with manipulation of the process of financial reporting by generating inadmissible (unanticipated work plan accounts, regulatory requirements) conduct. This situation may occur during the reporting period or at the end of the reporting period. Therefore, for identification of fraudulent actions, it is recommended that staff conduct a test of journal operations through the identification of transactions with unconnected, unusual or rarely used accounts, correspondent accounts that do not meet the requirements of the Instruction on application of the plan of accounts of assets, liabilities and capital № 291 of 30.11.1999 with changes and additions; a post-paid by employees who usually do not perform certain operations and at unusual times; at the end of the period or made after closing accounts that have no or practically no explanation or description; which contain rounded numbers or with clearly artificially calculated end numbers – 000 000, 111 111. The testing of the journal is realized by using Microsoft Excel from the Microsoft Office suite.